2016
DOI: 10.5194/hess-20-1765-2016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of land-use land-cover change on Indian summer monsoon daily rainfall and temperature during 1951–2005 using a regional climate model

Abstract: Abstract. Daily moderate rainfall events, which constitute a major portion of seasonal summer monsoon rainfall over central India, have decreased significantly during the period 1951 through 2005. On the other hand, mean and extreme near-surface daily temperature during the monsoon season have increased by a maximum of 1–1.5 °C. Using simulations made with a high-resolution regional climate model (RegCM4) and prescribed land cover of years 1950 and 2005, it is demonstrated that part of the changes in moderate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 86 publications
2
31
0
Order By: Relevance
“…There could be several factors contributing to the enhanced skill in surface temperature over India on sub-seasonal to seasonal time scales, such as the ocean (Pokhrel et al, 2015), snowmelt and associated hydrological effect over Eastern Eurasia (Halder and Dirmeyer, 2017) or land-use land-cover changes (Halder et al, 2016) that needs further investigation. Here, we explore the LA coupling pathway that links skill in local soil moisture anomalies to that of temperature and precipitation.…”
Section: Plausible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…There could be several factors contributing to the enhanced skill in surface temperature over India on sub-seasonal to seasonal time scales, such as the ocean (Pokhrel et al, 2015), snowmelt and associated hydrological effect over Eastern Eurasia (Halder and Dirmeyer, 2017) or land-use land-cover changes (Halder et al, 2016) that needs further investigation. Here, we explore the LA coupling pathway that links skill in local soil moisture anomalies to that of temperature and precipitation.…”
Section: Plausible Mechanismsmentioning
confidence: 99%
“…The central and northwestern parts of India constitute one of the global "hot spots" of land-atmosphere coupling where soil moisture anomalies exert a significant control on temperature and precipitation via strongly coupled processes Guo et al, 2006;Dirmeyer, 2011;Halder et al, 2015). In addition, efforts to investigate the role of land-surface processes during the onset (Saha et al, 2011(Saha et al, , 2017Bollasina and Ming, 2013;Senan et al, 2016) and in the low-frequency variability of the Indian summer monsoon (Webster, 1983;Ferranti et al, 1999;Yasunari, 2007;Turner and Slingo, 2011;Saha et al, 2012;Halder et al, 2015Halder et al, , 2016Halder and Dirmeyer, 2017) have further added to the confidence that the prediction skill of the Indian summer monsoon can be further improved. However, the actual prediction skill arising from anomalies in the land surface state may depend on the methods of forecast initialization (Dirmeyer, 2005;Koster et al, 2011), errors in land surface initial conditions Halder, 2016, 2017) and the systematic errors in the model (Dirmeyer, 2003) that affect the land-atmosphere (LA) coupling strength (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Surface vegetation changes affect the concentration of greenhouse gases and aerosols in the atmosphere through the interaction of energy balance, water vapor exchange, and biogeochemical cycles between the ground and the atmosphere, which in turn affects climate change [15][16][17][18][19][20][21][22][23][24]. The state of vegetation growth is critical to the health of terrestrial ecosystems and biospheres, and is closely related to the rainfall [25].…”
Section: Introductionmentioning
confidence: 99%
“…31 . Moreover, using high-resolution regional climate model (RegCM4) simulations and prescribed land cover of years 1950 and 2005, it is demonstrated that part of the changes in moderate rainfall events and temperature have been caused by LULCC 32 (Halder et al . 32 On the other hand, a recent study by Joshi and Rai 33 reported that the opposite phases of AMO and IPO together modulates the total/moderate rainfall over west central and northeast regions in an asymmetric manner; whereas their warm phase stimulates the heavy rainfall over west central region, while their opposite phases together influences the precipitation extremes over the northeastern region.…”
Section: Introductionmentioning
confidence: 99%